A case of simultaneous diagnosis of tunica vaginalis testis and pleural mesothelioma. Issue 4 (22nd March 2022) - Matsuki, Rei; Ishii, Satoru; Suzuki, Tomoyuki; Sugiyama, Haruhito
Abstract: A 37‐year‐old man was admitted to our hospital with chest pain and fever. Computed tomography showed pleural effusion and irregularly marginated, elevated lesions inside diffuse pleural thickening. Detailed medical examination showed swelling of the left testicle. 18F‐fluorodeoxyglucose positron emission tomography showed uptakes at the thickened pleura and left testis. Pelvic magnetic resonance imaging showed a mass in the left testis with a heterogeneous and partially calcified tumour present interiorly. Thoracoscopy was performed under local anaesthesia, enabling the observation of masses at the pleura and biopsy of the mass, which was diagnosed as malignant pleural mesothelioma. The affected testicle was resected and diagnosed as tunica vaginalis testis mesothelioma. Thus, simultaneous tunica vaginalis testis and pleural mesothelioma were diagnosed. It is necessary to closely examine parts of the body other than the chest. Abstract : Malignant pleural mesothelioma is one of the most severe diseases with a poor prognosis. Pulmonologists often make diagnoses of pleural mesothelioma with a history of asbestos exposure. It mainly involves the pleura, but can arise in other places, such as the tunica vaginalis testis. Thus, a case of simultaneous diagnosis of tunica vaginalis testis mesothelioma and malignant pleural mesothelioma is reported.